Water erosion due to maximum rainfall at different return times in the Cumbaza sub-basin - San Martín Region - Camacho-Zorogastúa, Katherine (2019)
The Cumbaza Sub-basin has the largest amount of forested areas (primary forests) deforested, which has generated the increase of water erosion in soils. The present investigation had as objective know the water erosion in function of the maximum rains for different times of return by means of the Model of the Universal Equation of Loss of Soils and the modeling of the Geographic Information Systems (GIS), in order to propose measures of soil conservation. An empirical investigation of non-experimental design was carried out, for which the maximum rains were evaluated in 24 hours through hydrological regionalization using the Gumbel Type I method, to know the rainfall distribution in Cumbaza, then the thirteen were evaluated cartographically (13 ) areas of erosive vulnerability using GIS modeling, making a weighting, of which 23.2% of the total area presents a high erosive vulnerability, while 58.1% have an average vulnerability, and 12.1 and 6, 6% have low and very low vulnerability, respectively. Likewise, the water erosion rate was estimated using the USLE model, resulting in values of 31, 40 and 50 t / ha / year for a return time of 5, 25 and 100 years respectively; and finally, a proposal was formulated for the conservation of soils using Agroforestry Systems through reforestation with native species depending on the type of soil, climate, altitude, costs, etc., for which nativetrees and shrubs were used, such as Aguaje, Bamboo Caoba, Ojé and Sacha Inchi.